2023
DOI: 10.1007/s11082-022-04516-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced optical and thermal conductivity properties of barium titanate ceramic via strontium doping for thermo-optical applications

Abstract: In this study, we prepared a homogeneous fine powder of barium titanate (BaTiO3, BT) doped with different concentrations of strontium (x = 0, 0.05, 0.125, 0.15, 0.20, and 0.3) and having the composition Ba1-xSrxTiO3 (barium strontium titanate, BSrxT). XRD patterns and Rietveld refinement revealed the existence of a single tetragonal phase structure for BSrxT, x = 0–20%, and a single cubic structure for BSr30%T. The physical properties of the pure and doped mixtures were studied. The results showed that the add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Perovskite ceramic materials are attracting huge interest nowadays due to their fascinating properties, which lead to different optoelectronic applications (Tihtih et al 2021(Tihtih et al , 2023Ibrahim et al 2017Ibrahim et al , 2019Lökçü 2013). One of these applications includes microwave shielding (Pratap et al 2018(Pratap et al , 2021Peymanfar et al 2020aPeymanfar et al , 2021a.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite ceramic materials are attracting huge interest nowadays due to their fascinating properties, which lead to different optoelectronic applications (Tihtih et al 2021(Tihtih et al , 2023Ibrahim et al 2017Ibrahim et al , 2019Lökçü 2013). One of these applications includes microwave shielding (Pratap et al 2018(Pratap et al , 2021Peymanfar et al 2020aPeymanfar et al , 2021a.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of the BaTiO 3 NTs electrode was estimated to be 44.43 μA mM −1 cm −2 . From figures 6 and 8, it was observed that fabricated BTNTs sensor-based electrode had shown high sensitivity, lesser response time and good linearity compared with other reported ones on BaTiO 3 -based glucose sensors [16].…”
Section: K Cos L B Q =mentioning
confidence: 85%
“…Among the metal oxides, nanostructures of BaTiO 3 have been intensively investigated owing to their excellent properties such as large surface to volume ratio, high thermal and chemical stabilities, good biocompatibility, low-cost, lead-free, excellent piezoelectric as well as ferroelectric properties [8][9][10][11]. Due to these, BaTiO 3 nanostructures suitable for many applications such as multilayer ceramic capacitors, nanogenerators, microwave absorbers, thermo optical applications, energy/data storage devices, transducers, resonators, actuators, nonvolatile random-access memory devices, biosensors, hydrophobic coatings, etc [12][13][14][15][16][17][18][19][20][21][22]. However, only a few reports have been reported on glucose sensing and hydrophobic nature of BaTiO 3 nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…For both samples, the phase transition temperature is between 110 and 100 K. Our data show that the Mn 2+ -doping in Cs 2 NaBiCl 6 does not change the phase transition behavior. There are instances in literature where lattice doping of perovskites can significantly change the transition temperature from the tetragonal to cubic phase, but this occurs at a higher (4–7%) doping concentration. , In Mn 2+ -doped Cs 2 NaBiCl 6 , the dopant concentration relevant for Mn 2+ PL is small (0.1–1.3%, see Figure d), and the doping does not significantly alter the phase transition behavior.…”
Section: Resultsmentioning
confidence: 99%